Second molar scissor bite correction in class ii malocclusion using miniscrew and cross-elastic - Citra L. Yuwono; Retno Widayati (Journal of Dentomaxillofacial Science, 2022)
Objective: Scissor bite is one of the atypical findings that could be found in daily practice, especially in Class II malocclusion. The aim was to report second molar scissor bite correction using miniscrew and cross-elastic. Methods: A 20 years-old, female, had second molar scissor bite with Class II malocclusion. Extrusion and buccoversion of the upper left second molar were noted with lingual tipping of bilateral lower second molar. Deep bite and mild crowding were found with missing upper first premolar and lower anterior tooth gemination. A miniscrew was placed to intrude the extruded second molar, while additional cross-elastic was used to correct both upper and lower teeth position. Results: Combination of miniscrew and cross-elastic successfully correct second molar scissor bite in seven months through intrusion and palatal tipping of upper molar and uprighting of the lower molar. With a total treatment of twenty-three months, a good intercuspation was achieved with Class I canine, Class II molar relationship, and normal overjet and overbite Conclusion: The use of miniscrew with cross-elastic successfully correct second molar scissors bite in Class II malocclusion.